2020
DOI: 10.1038/s41419-020-02801-6
|View full text |Cite
|
Sign up to set email alerts
|

The miR-1224-5p/TNS4/EGFR axis inhibits tumour progression in oesophageal squamous cell carcinoma

Abstract: Oesophageal squamous cell carcinoma (ESCC) is a common and aggressive malignancy. Although many molecular alterations have been observed in ESCC, the mechanisms underlying the development and progression of this disease remain unclear. In the present study, miR-1224-5p was identified to be downregulated in ESCC tissues compared to normal tissues, and its low expression was correlated with shorter survival time in patients. In vitro experiments showed that miR-1224-5p inhibited the proliferation, colony formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…For example, miR-148a might play its oncogenic role by targeting AVR1 in ESCC ( 16 ). miR-1224-5p inhibits tumor progression by targeting the TNS4/EGFR axis ( 17 ). There are also several types of research confirmed the oncogenetic roles of miR-17-5p.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-148a might play its oncogenic role by targeting AVR1 in ESCC ( 16 ). miR-1224-5p inhibits tumor progression by targeting the TNS4/EGFR axis ( 17 ). There are also several types of research confirmed the oncogenetic roles of miR-17-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that TNS4 may be involved in the pathogenesis of cancers by interacting with miRNAs. For instance, miR-1224-5p inhibits TNS4, subsequently affecting the progression of oesophageal squamous cell carcinoma[ 36 ]. According to a recent report, TNS4 was identified as a key effector of cetuximab and a regulator of the oncogenic activity of KRAS mutant CRC[ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1224-5p played an anti-cancer role in various cancers, such as rectal cancer [ 41 ], pancreatic cancer [ 42 ], ovarian cancer [ 43 ], and glioma [ 44 ]. In addition, a report from Shi et al also elucidated that miR-1224-5p could impair the development of esophageal squamous cell carcinoma, which is another HNSC subtype [ 45 ]. In the current study, miR-1224-5p was targeted and negatively regulated by APCDD1L-AS1 in OSCC cells resistant to 5-FU.…”
Section: Discussionmentioning
confidence: 99%